The contribution of health risk behaviors to excess mortality in American adults with chronic hepatitis C: A population cohort‐study. Issue 1 (16th November 2017) - Innes, Hamish; McAuley, Andrew; Alavi, Maryam; Valerio, Heather; Goldberg, David; Hutchinson, Sharon J.
Abstract : In resource‐rich countries, chronic hepatitis C (CHC) infection is associated with a sizeable excess mortality risk. The extent to which this is due to (1) the biological sequelae of CHC infection versus (2) a high concomitant burden of health risk behaviors (HRBs) is unclear. We used data from the 1999‐2010 U.S. National Health and Nutritional Examination Surveys (NHANES), which include detailed information on HRBs and CHC infection status. We calculated the prevalence of the five major HRBs—alcohol use; cigarette smoking, physical inactivity, unhealthy diet, and illicit drug use—according to CHC after adjusting for sociodemographic differences. Mortality status after survey interview was ascertained by linkage to the U.S. National Death Index. To assess the contribution of HRBs to the excess mortality risk, we determined the all‐cause mortality rate ratio (MRR) for individuals with CHC relative to individuals without, and then calculated the attenuation in this MRR following adjustment for HRBs. This analysis included 27, 468 adult participants of NHANES of which 363 tested positive for CHC. All HRBs were markedly more prevalent among individuals with CHC versus individuals without. CHC was associated with a 2.4‐fold higher mortality rate after adjustment for sociodemographic factors (MRR, 2.36; 95% CI, 1.60‐3.49). Subsequent adjustment for all five HRBs attenuated this ratio by 50.7% to MRR 1.67 (95% CI, 1.14‐2.44). Higher levels of attenuation (69.1%) were observed among individuals aged 45‐70 years, who form the target demographic for U.S. birth cohort screening. Conclusion: At least half the excess mortality risk for individuals with CHC in the United States may be attributed to HRBs rather than CHC. The remedial response to hepatitis C must not neglect action on HRBs if it is to fully resolve the high mortality problem in this population. (Hepatology 2018;67:97‐107).